The clinical impact of staging bone marrow examination on treatment decisions and prognostic assessment of lymphoma patients. (29th April 2015) - Painter, Dan; Smith, Alexandra; de Tute, Ruth; Crouch, Simon; Roman, Eve; Jack, Andrew
Summary This study investigates the value of performing a staging bone marrow in patients with diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL) and classical hodgkin lymphoma (CHL). The results of 3112 staging bone marrow examinations were assessed for impact on prognostic assessment and critical treatment decisions. The detection of marrow involvement altered the disease‐specific prognostic index for 4·3% of DLBCL, 6·2% of FL and 0·6% of CHL but marrow involvement in DLBCL was an independent prognostic factor. Knowing the marrow status potentially changed treatment in 92 patients, detection of these patients would have required 854 examinations to be performed.